Cell Surface Receptor Targeted Biomimetic Apatite Nanocrystals for Cancer Therapy. Issue 22 (18th April 2013) - Iafisco, Michele; Delgado‐Lopez, Josè Manuel; Varoni, Elena Maria; Tampieri, Anna; Rimondini, Lia; Gomez‐Morales, Jaime; Prat, Maria
Abstract Nanosized drug carriers functionalized with moieties specifically targeting tumor cells are promising tools in cancer therapy, due to their ability to circulate in the bloodstream for longer periods and their selectivity for tumor cells, enabling the sparing of healthy tissues. Because of its biocompatibility, high bioresorbability, and responsiveness to pH changes, synthetic biomimetic nanocrystalline apatites are used as nanocarriers to produce multifunctional nanoparticles, by coupling them with the chemotherapeutic drug doxorubicin (DOXO) and the DO‐24 monoclonal antibody (mAb) directed against the Met/Hepatocyte Growth Factor receptor (Met/HGFR), which is over‐expressed on different types of carcinomas and thus represents a useful tumor target. The chemical‐physical features of the nanoparticles are fully investigated and their interaction with cells expressing (GTL‐16 gastric carcinoma line) or not expressing (NIH‐3T3 fibroblasts) the Met/HGFR is analyzed. Functionalized nanoparticles specifically bind to and are internalized in cells expressing the receptor (GTL‐16) but not in the ones that do not express it (NIH‐3T3). Moreover they discharge DOXO in the targeted GTL‐16 cells that reach the nucleus and display cytotoxicity as assessed in an MTT assay. Two different types of ternary nanoparticles are prepared, differing for the sequence of the functionalization steps (adsorption of DOXO first and then mAb or vice versa), and it is found that the ones in which mAb is adsorbed first are more efficient under all the examined aspects (binding, internalization, cytotoxicity), possibly because of a better mAb orientation on the nanoparticle surface. These multifunctional nanoparticles could thus be useful instruments for targeted local or systemic drug delivery, allowing a reduction in the therapeutic dose of the drug and thus adverse side effects. Moreover, this work opens new perspectives in the use of nanocrystalline apatites as a new platform for theranostic applications in nanomedicine.